Half a century (1954–2009) of dissection data of sea urchins from the North American Pacific coast (Mexico–Canada): Ecological Archives E094‐193. Issue 9 (1st September 2013) - Ebert, T. A.; Hernández, J. C.; Clemente, S.; Russell, M. P.; Basch, L. V.; Boolootian, R. A.; Detwiler, P. M.; Kenner, M. C.; Lawrence, A. L.; Lawrence, J. M.; Leighton, D. L.; Palleiro, J. S.; et al.
Abstract : Total body size, mass or linear measurements, and gonad mass or volumes have been recorded for the North American Pacific coast sea urchins Strongylocentrotus purpuratus, Mesocentrotus (Strongylocentrotus) franciscanus, and Lytechinus pictus by various workers at diverse sites and for varying lengths of time from 1954 to 2009. Some dissections included other body components such as the gut, body wall, and Aristotle's lantern, and some dissections included both wet and dry mass. There are numerous peer‐reviewed publications that have used some of these data, but some data have appeared only in graduate theses or in the gray literature. There also are data that have never appeared outside the original data sheets. Historically, data were used to describe reproductive cycles and then to compare responses to stressors such as food limitation or pollution. Differences in temperature among sites also have been explored. More recently, dissection data have linked gonad development to ocean conditions, so called bottom‐up forcing. The data set presented here is a historical record of gonad development for a common group of marine invertebrates in intertidal and nearshore environments, which can be used to test hypotheses concerning future changes associated with climate change and ocean acidification along the Pacific Coast of North America.